Cisplatin/Tegafur/Uracil/Irinotecan Triple Combination Therapy for Recurrent/Metastatic Head and Neck Squamous Cell Carcinoma: A Phase I/II Clinical Study. (18th April 2016) - Chen, San-Chi; Chang, Peter Mu-Hsin; Yang, Muh-Hwa
Abstract: Lessons Learned: Cisplatin/tegafur/uracil/irinotecan triple combination therapy shows moderate response, especially in patients without previous chemoradiotherapy within the 6 months before this combination therapy. Toxicity is tolerable, and quality of life is improved in responders. Background: The prognosis is poor in recurrent/metastatic head and neck squamous cell carcinoma (R/M HNSCC). Triple combination therapy may increase tumor response. Methods: This phase I/II prospective trial first determined the dose-limiting toxicity and recommended dose of irinotecan with cisplatin and tegafur/uracil (UFUR) in phase I. Irinotecan was supplied at doses of 40, 50, 60, and 70 mg/m 2 by using a standard 3+3 design. Doses of cisplatin and UFUR were held stable. In phase II, the recommended dose of irinotecan was administered intravenously (i.v.) over 90 min on day 1, with cisplatin 50 mg/m 2 i.v. over 60 min also on day 1, and oral UFUR 200 mg twice a day for 5 days every 2 weeks a cycle. Results: In the phase I portion, 14 patients were enrolled, and the dose level of irinotecan at 60 mg/m 2 was defined as the recommended dose for the phase II portion of the study. Among 43 patients enrolled in the phase II portion, complete response was seen in 2 patients (4.7%) and partial response in 10 patients (23.3%), and the disease control rate was 39.5%. In a subgroup analysis of patients whose prior chemoradiotherapy was more than 6 months earlier, a response rate of 40.7% and disease control rate of 59.3% were observed. Conclusion: Cisplatin/UFUR/irinotecan triple combination therapy is tolerated and effective for selected patients. Individualized choice of treatment will influence prognosis and quality of life in R/M HNSCC patients.